2019
DOI: 10.1080/10967494.2019.1668895
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the impact of co-production on pathways to outcomes in public services: the case of policing and criminal justice

Abstract: There has recently been an upsurge of interest in the role of co-production in public services.This paper focuses on how the capabilities of public service users and other citizens can improve the outcomes of public services such as policing and the criminal justice system, where the role of citizens is altering significantly. The paper develops a model of pathways to public service outcomes, showing the connections between citizen co-production and the core activities in policing and criminal justice, in line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
5

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 44 publications
0
32
0
5
Order By: Relevance
“…According to Vanleene, Verschuere, and Voets (2015), the outcomes of coproduction can be divided into different clusters. Building on this idea, the following five rationales are identified by the present study as overall outcomes that represent the logic for adopting co-production as an organisational recipe (Mortensen, forthcoming): 'realisation of innovation potential' (Pestoff and Brandsen 2010;Osborne, McLaughlin, and Chew 2008;Lindsay, Osborne, and Bond 2014;Osborne, Radnor, and Strokosch 2016), 'better individual well-being and citizen empowerment' (Jo and Nabatchi 2018;Needham 2008;Bovaird and Loeffler 2012), 'increased effectiveness and efficiency' (Vanleene, Verschuere, and Voets 2015), 'mobilisation of resources' (Bovaird 2007;Loeffler and Bovaird, forthcoming), and 'increased democracy' (Verschuere et al 2018;Pestoff 2009; Vanleene, Verschuere, and Voets 2015). These rationales do not represent a comprehensive list but draw on the different theoretical arguments for co-production in the public sector (Pestoff 2019).…”
Section: Co-production Definitions and Outcomesmentioning
confidence: 95%
See 1 more Smart Citation
“…According to Vanleene, Verschuere, and Voets (2015), the outcomes of coproduction can be divided into different clusters. Building on this idea, the following five rationales are identified by the present study as overall outcomes that represent the logic for adopting co-production as an organisational recipe (Mortensen, forthcoming): 'realisation of innovation potential' (Pestoff and Brandsen 2010;Osborne, McLaughlin, and Chew 2008;Lindsay, Osborne, and Bond 2014;Osborne, Radnor, and Strokosch 2016), 'better individual well-being and citizen empowerment' (Jo and Nabatchi 2018;Needham 2008;Bovaird and Loeffler 2012), 'increased effectiveness and efficiency' (Vanleene, Verschuere, and Voets 2015), 'mobilisation of resources' (Bovaird 2007;Loeffler and Bovaird, forthcoming), and 'increased democracy' (Verschuere et al 2018;Pestoff 2009; Vanleene, Verschuere, and Voets 2015). These rationales do not represent a comprehensive list but draw on the different theoretical arguments for co-production in the public sector (Pestoff 2019).…”
Section: Co-production Definitions and Outcomesmentioning
confidence: 95%
“…Proposed outcomes of co-production: five rationales Scant empirical studies have reported on the outcomes of co-production (Voorberg, Bekkers, and Tummers 2015;Loeffler and Bovaird, forthcoming). A review by Voorberg, Bekkers, and Tummers (2015) determined that 80% of the studies labelling themselves as addressing co-production did not focus on the outcomes of co-production.…”
Section: Co-production Definitions and Outcomesmentioning
confidence: 99%
“…The rst group comprises antecedents that limit the effectiveness of the 'interactional process' due to the lack of resources by consumers and/or providers. This group includes consumers the lack of technical information [16], knowledge of users' needs and expectations [19], transparency and understanding of each other parties' roles and responsibilities [15], trust [37] and public investment [25]. The second group of antecedents of co-destruction consists of limitations related to the context of analysis such as rigidities of the public service organizations [19].…”
Section: Co-destruction In the Public Sectormentioning
confidence: 99%
“…The last group comprises antecedents that encourage misbehaviours in participants during and after the interaction process. This group includes misbehaviour by participants such as corruption, infringement of privacy, discrimination [25], listlessness and denial [6,19].…”
Section: Co-destruction In the Public Sectormentioning
confidence: 99%
See 1 more Smart Citation